Nivolumab and Hypofractionated Radiotherapy in Patients With Advanced Lung Cancer: ABSCOPAL-1 Clinical Trial - Ye, Hua; Pang, Haowen; Shi, Xiangxiang; Ren, Peirong; Huang, Shangke; Yu, Hong; Wu, Jingbo; Lin, Sheng (Frontiers in Oncology, 2021)
BACKGROUND:More clinical practice need to be performed to verify the toxicity of the hypofractionated radiotherapy (HFRT) combined with PD-1 blockade in lung cancer. This phase I study aimed to investigate the safety and efficacy of nivolumab combined with HFRT in patients with progressive advanced lung cancer following multiline treatment. METHODS: We evaluated 31 patients with advanced lung cancer pathologically confirmed to have progressive disease and treated with first-line or a higher therapy. Selected lesions were treated using HFRT, and nivolumab was administered within 7 days subsequently. Nivolumab was administered once a month following partial remission. Peripheral blood was collected before and after 1 month of treatment to evaluate relevant cytokines between nivolumab responders and non-responders. RESULTS: Overall, 23 patients who completed the treatment were evaluated. Of them, 9 and 14 patients underwent hypofractionated brachytherapy with 30 Gy in a single fraction via percutaneous interstitial implantation of 192Ir and 40–50 Gy in 5 fractions via stereotactic body radiation therapy, respectively. The median follow-up period was 11 months. At the 1-year follow-up, no patient developed grade ≥ 3 pneumonitis. The overall objective response and complete remission rates were 39.13% and 13.04%, respectively. The 1-year overall survival and median progression-free survival were 60.9% and 6 months, respectively. The plasma levels of interleukin IL-6, IL-10, and IL-17A were significantly reduced after treatment in nivolumab responders. CONCLUSIONS: HFRT could increase the responsivity to nivolumab and reduce its administration frequency. This combination treatment is well tolerated with acceptable toxicity and thus merits further trials to validate benefits.